A REVIEW ON BHASHA LAKSHANAAMRUTHAM - Aravind Nath; Acharya Niranjana (International Journal of Applied Ayurved Research, 2020)
Agada Tantra is a branch of Ayurveda which deals with identification, prevention, diagnosis and treatment of various animate, inanimate, subclinical, residual and cumulative poisons. The tradition of Agada Tantra practice is very ancient and which can be considered under emergency management in Ayurveda. Agada Tantra was so popular in Kerala and lot of texts were written in various local languages and were practiced extensively. Bhasha Lakshanaamrutham among them which is a Malayalam translation of the text Lakshanaamrutham. Lakshanaamrutham is considered as the one of the seven famous books of Agada Tantra which is currently unavailable. Bhasha Lakshanaamrutham is very concise and is in Padya form which is easy to read and understand. Unfortunately the text is not translated into English and it’s very rare to get. So this article aims to do a review on hidden knowledge of Visha Chikitsa from this book.